منهج تعليم اللغة العربية في المعهد باب السلام موجواجونج جومبانج - Nasiruddin, Muhammad (el Buhuth: Borneo Journal of Islamic Studies, 2021)
Abstract his study aims to determine the Arabic language learning curriculum, its implementation as well as its advantages and disadvantages in Pondok Pesantren Babussalam Mojoagung Jombang. By using descriptive qualitative research methods, from the two lodges the researcher found differences in terms of the orientation of Arabic learning and teaching materials for students in the field of Arabic. The results of the research are: 1) the Arabic language learning curriculum at the Islamic Boarding School functionally acts as a guide, instrument and benchmarks to determine the success of learning, by fulfilling the curriculum elements, namely objectives, content / teaching materials, learning activities and evaluation. The four elements are arranged according to the needs and levels of students. 2) In implementing the curriculum, there is a special curriculum in accordance with the Arabic language learning orientation at the Islamic boarding school. 3) The strengths of the Arabic language learning curriculum at the cottage are that the curriculum is both designed according to the needs and ability levels of students, namely middle-level students. The drawback of the Arabic learning curriculum at Pondok Pesantren Babussalam Mojoagung Jombang is that there is no learning plan in the form of developing an Arabic syllabus. Meanwhile, the Basussalam Islamic boarding school uses the modern Islamic boarding school model in Arabic language learning Keywords: curriculum, Arabic language learning.  ملخصتهدف هذه الدراسة إلى معرفة المنهج الدراسي في تعليم اللغة العربية، وتطبيقه، ومزاياه ونقصانه في المعهد باب السلام موجوأجونج جومبانج. باستخدام منهج البحث الكيفي والوصفي فوجد الباحث من حيث الاتجاهات في تعليم اللغة العربية ذلك المعهد نتائج الدراسة كما يلي: 1) يساهم المنهج الدراسي لتعليم اللغة العربية في ذلك المعهد وظيفياً كالدليل والوسيلة والمعيار لمعرفة نجاح التعليم، متكامل العناصر من الأهداف والمحتويات والأنشطة التعليمية والتقويم. ويتم هذه العناصر الأربعة للمنهج الدراسي وفقاً لاحتياجات الطلاب ومستوياتهم، 2) هناك التطوير للمنهج الدراسي الخاص في تطبيق المنهج الدراسي لتعليم اللغة العربية يتلائم مع الاتجاهات في تعليم اللغة العربية في ذلك المعهد، 3) تتمثل المنهج الدراسي لتعليم اللغة العربية في ذلك المعهد من ناحية المزايا وهو المنهج الدراسي المصمم وفقاً لاحتياجات الطلاب ومستوى قدراتهم. والنقصان في المنهج الدراسي لتعليم اللغة العربية في المعهد باب السلام جومبانج هو عدم التخطيط التعليمي من القررات الدراسية في عملية التعليم تطويرياً ويستخدم بأسلوب المعهد في تعليم اللغة العربية.        الكلمات الأساسية: المنهج ،تعليم اللغة العربية.